THE TUBERCULOSIS AND HIV INFECTION SITUATION IN RUSSIA - O. B. Nechaeva (Туберкулез и болезни лёгких)
The tuberculosis and HIV infection epidemic situation in 2009-2012 was studied. In 2012, the incidence of tuberculosis in HIV-infected patients among the resident population registered in 2012 was 35 times higher, its prevalence at the end of the year was 32 times higher, and its mortality rates were 28 times higher than the average Russian rates. Mortality rates in patients with HIV infection were directly related to the prevalence of tuberculosis in a region.The impact of HIV infection on the epidemic process in tuberculosis will increase. By 2020, among the first registered tuberculosis patients, there will be as high as 30% with HIV infection in Russia as a whole and as high as 40-50% in individual subjects of the Russian Federation. The procedure and time of prophylactic examinations of HIV-infected patients to detect tuberculosis are not observed although there has been recently an increase in examination coverage (79.4% in 2012). Tuberculosis chemoprophylaxis is made only in late-stage (4B, 4C, and 5) HIV infection only in one-third of the indicated cases.It is necessary to continue organizational work to set up specialized tuberculosis departments, including that with surgical methods, to treat patients with tuberculosis concurrent with HIV infection.